Level of perception on fertigation technology among Indigenous people in Perak, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2024)
Fertigation technology has proven to be a successful method for enhancing crop yields by applying nutrients. It is cost-effective, easy to install, and simple to operate, which is why many farmers in Malaysia have adopted it. However, indigenous people have hesitated to use it due to negative perceptions. This study aims to determine the level of perception of indigenous people in Perak towards fertigation technology. The study uses a quantitative approach based on the Theory of Planned Behavior (TPB), with attitude, subjective norm, and perceived behavioural control as independent variables and perception towards fertigation technology as the dependent variable. A purposive sampling technique was used to select 150 respondents, and descriptive analysis was employed for data analysis. The findings demonstrate that the mean score for indigenous people's perception of fertigation technology was moderate (M = 2.7667, SD = 0.87774) including their attitude (M = 2.5875, SD = .94309). While subjective norm (M = 2.3343, SD = 0.90242), and perceived behavioural control (M =2.3933, SD = .86919) have a low mean score. These empirical findings provide valuable insights for policy-makers to help indigenous people adapt to modern technology and boost their economic growth, especially into actionable strategies that facilitate the adaptation of indigenous people to modern agricultural practices while respecting their cultural identity and promoting sustainable development.
Keywords: perception; indigenous people; fertigation technology; TPB theory